1Institute of Biotechnology, Vietnam Academy of Science and Technology - Dũng, Nguyễn Tiến; Anh, Đỗ Thị Vân; Phương, Nguyễn Thị Minh; Huyền, Bùi Thị; Minh, Phạm Đình; Chí, Đỗ Hữu; Liên, Nguyễn Thị Phương; Chi, Phan Văn; Thảo, Lê Thị Bích (Vietnam Journal of Biotechnology, 2018)
Wasp venoms are complex mixtures of various types of compounds, of which proteins and peptides are major components. Beside its toxicity, wasp venom is potential for treatment of diseases. Characterization of venom proteins and peptides is the first and most important step toward its applications in medicine. Vietnam possesses many valuable materials, of which venoms could be used in medicine. In the present work, we aim to identify proteins and peptides in the venom of Vespa velutina (V. velutina), a species of social wasp indigenous to Southeast Asia including Vietnam using proteomic techniques. The venom isolated from V. velutina by manual extraction was digested with trypsin via the FASP (Filter Aided Sample Preparation) method and analyzed with liquid chromatography tandem - mass spectrometry (LC-MS/MS). The following protein identification, protein validation, and peptide de novo sequencing were carried out using the Peaks software. In total, we detected 36 proteins from V. velutina venom and many of them had been reported as venom-specific proteins. According to Gene Ontology Annotation (GOA), V. velutina venom proteins were functionally classified into five categories: binding proteins (53%), catalytic proteins (33%), structural proteins (8%), antioxidants (4%), and proteins with other functions (2%). In addition, 81 peptides were detected in the venom of V. velutina by de novo sequencing, of which 34 peptides (42%) are potential venom peptides. We introduced for the first time the collection of proteins and peptides from V. velutina venom, providing the basis for its further application in medicine.